An evaluation of response prompts for teaching behavior chains. Issue 4 (10th October 2014) - Seaver, Jessica L.; Bourret, Jason C.
<x xml:space="preserve">Abstract</x> Individuals who have been diagnosed with autism spectrum disorders can have difficulty acquiring new skills, and teaching procedures found to be efficient with 1 individual may not be efficient with others. However, relatively little research has evaluated methods to identify efficient, individualized response‐prompt and prompt‐fading procedures. We evaluated an assessment of multiple response prompts and prompt‐fading procedures with 10 individuals with an autism spectrum disorder. The prompt types assessed were verbal and gestural, model, and physical. Prompt‐fading procedures assessed were least to most, most to least, and a progressive delay. Each assessment was conducted at least twice, and the findings of both prompt‐type and prompt‐fading assessments were generally reliable. A final validity test showed the assessment outcomes to have generality that may extend to other clinically significant responses.